Antitumor Efficacy of a Monoclonal Antibody That Inhibits the Activity of Cancer-Associated Carbonic Anhydrase XII - Gábor Gondi; Josef Mysliwietz; Alžbeta Hulı́ková; Jian Ping Jen; Pawel Swietach; Elisabeth Kremmer; Reinhard Zeidler (2013)
Carbonic anhydrase XII (CA XII) is a membrane-tethered cell surface enzyme that is highly expressed on many human tumor cells. Carbonic anhydrase members in this class of exofacial molecules facilitate tumor metabolism by facilitating CO2 venting and intracellular pH regulation. Accordingly, inhibition of exofacial CAs has been proposed as a general therapeutic strategy to target cancer. The recent characterization of 6A10, the first CA XII-specific inhibitory monoclonal antibody, offered an opportunity to evaluate this strategy with regard to CA XII-mediated catalysis. Using functional assays, we showed that 6A10 inhibited exofacial CA activity in CA XII-expressing cancer cells. 6A10 reduced spheroid growth in vitro under culture conditions where CA XII was active (i.e., alkaline pH) and where its catalytic activity was likely rate-limiting (i.e., restricted extracellular HCO3-supply). These in vitro results argued that the antibody exerted its growth-retarding effect by acting on the catalytic process, rather than on antigen binding per se. Notably, when administered in a mouse xenograft model of human cancer, 6A10 exerted a significant delay on tumor outgrowth. These results corroborate the notion that exofacial CA is critical for cancer cell physiology and they establish the immunotherapeutic efficacy of targeting CA XII using an inhibitory antibody.